WATER ALLOCATION OPTIMIZATION FOR SUPPLEMENTARY IRRIGATION IN RAINFED LANDS TO INCREASE TOTAL INCOME CASE STUDY: UPSTREAM KARKHEH RIVER BASIN1. (20th November 2012) - Ramezani Etedali, Hadi; Liaghat, Abdolmajid; Parsinejad, Masoud; Tavakkoli, Ali Reaz; Bozorg Haddad, Omid; Ramezani Etedali, Mojtaba
ABSTRACT Supplementary irrigation is an efficient strategy for improving yield and water use efficiency in rainfed agriculture. However, water allocation is a challenge because water resources are restricted. Therefore, water allocation management between irrigated and rainfed fields could be a viable strategy. Water resources for supplementary irrigation in rainfed fields are saved through deficit irrigation in irrigated lands. In this study, water allocation between irrigated and rainfed fields was optimized to maximize total economic income in Kermanshah and Lorestan provinces. Results showed that total income from grains and legumes increased by 443 000 and 397 000 million rials‡ in Kermanshah and Lorestan provinces, respectively. When saved water is applied used for supplementary irrigation only on grain rainfed fields, total income increased by 8.3 and 16.3%. When saved water was transported in between provinces and applied on rainfed fields, total income increased by 14.3% in both provinces. When transported water was applied as supplementary irrigation only on rainfed grain fields, total income increased by 11.3% in both provinces compared to the current situation. Copyright © 2012 John Wiley & Sons, Ltd.